2023
DOI: 10.3390/diagnostics13122083
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Non-Invasive Multimodality Imaging in Chronic Coronary Syndrome: Anatomical and Functional Pathways

Abstract: Coronary artery disease (CAD) is one of the major causes of mortality and morbidity worldwide, with a high socioeconomic impact. Currently, various guidelines and recommendations have been published about chronic coronary syndromes (CCS). According to the recent European Society of Cardiology guidelines on chronic coronary syndrome, a multimodal imaging approach is strongly recommended in the evaluation of patients with suspected CAD. Today, in the current practice, non-invasive imaging methods can assess coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…Finally, perfusion and functional cardiac imaging could enhance the accuracy of detecting CAD in subjects with high CVR, such as people with T1D. Resting global longitudinal strain has also been highlighted as an early marker of myocardial damage in people with chronic coronary syndromes, and stress echocardiography has been used to detect coronary artery disease burden [125,126].…”
Section: Other Screening Methodsmentioning
confidence: 99%
“…Finally, perfusion and functional cardiac imaging could enhance the accuracy of detecting CAD in subjects with high CVR, such as people with T1D. Resting global longitudinal strain has also been highlighted as an early marker of myocardial damage in people with chronic coronary syndromes, and stress echocardiography has been used to detect coronary artery disease burden [125,126].…”
Section: Other Screening Methodsmentioning
confidence: 99%
“…Following exercise or pharmacologically induced coronary artery dilation, SPECT imaging is used to identify areas of myocardium with hemodynamically significant perfusion deficits, visualized as a reduced radiotracer concentration [ 76 ]. When conducted with hybrid SPECT/CT machines, the concomitant assessment of LV volume and function may assist enhancing the diagnostic accuracy [ 77 ]. Studies have shown the incremental value of stress SPECT imaging over baseline rest SPECT imaging for the detection of CAV and potential prognostication [ 78 , 79 ].…”
Section: Non-invasive Modalitiesmentioning
confidence: 99%
“…So, CMR is also effective in assessing myocardial vitality through discrimination of the LGE extension and segmental kinesis and this can guide coronary revascularization [9]. There is a close relation between the percentage of the left ventricular wall thickness which is affected by the infarction scar and functional recovery after myocardial revascularization: wall segments with <25% LGE extension are more likely to regain contractility than segments with >50% LGE transmurality [10].…”
Section: Ischemic Cardiomyopathymentioning
confidence: 99%